2015
DOI: 10.1002/ceat.201400604
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Silica Removal by Polyamine‐ and Polyacrylamide‐Polyaluminum Hybrid Coagulants

Abstract: Silica removal is the main bottleneck for a high reuse of deinking paper mill effluents due to silica scaling on the reverse‐osmosis units generally used. The efficiency of inorganic‐organic hybrid coagulants formed by the combination of polyaluminum nitrate sulfate (PANS) with different dosages of cationic polyacrylamide (PAM) or polyamines (PA) on silica removal is analyzed. These hybrids significantly increased the silica and chemical oxygen demand (COD) removal at all pH values studied, with PA modificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…The sporadic rise in EC observed in all the samples tested could be due to the presence of the dissolved ions of the wastewater coupled with the dissolved ions of the coagulants and the pH regulator (NaOH). Similar observations have been made by other researchers [49,50].…”
Section: Effect Of the Coagulants On Electric Conductivitysupporting
confidence: 92%
“…The sporadic rise in EC observed in all the samples tested could be due to the presence of the dissolved ions of the wastewater coupled with the dissolved ions of the coagulants and the pH regulator (NaOH). Similar observations have been made by other researchers [49,50].…”
Section: Effect Of the Coagulants On Electric Conductivitysupporting
confidence: 92%
“…Polyaluminum chlorides (PACs), as well as polyaluminum nitrate sulfate (PANS), have been extensively used in the last decades for wastewater treatment in the paper industry (Pernitsky and Edzwald 2006;Miranda et al 2009bMiranda et al , 2015. These products can be modified with organic polymers to create inorganic-organic hybrids or composite coagulants, which improve the coagulation performance of the inorganic salts alone due to the synergy between the individual components (Lee et al 2012;Latour et al 2015).…”
Section: Hybrid Coagulantsmentioning
confidence: 99%
“…Previous studies have demonstrated that the coagulants with the highest efficiency in removing COD were usually those with the lowest efficiency in silica removal, and vice versa (Hermosilla et al, 2012;Latour et al, 2013;Miranda et al, 2015b). However, the reason for this was not established.…”
Section: Soluble Silicamentioning
confidence: 94%